The Indian Rural Market: Emerging Opportunities and Challenges - Azhar Suharwardi, Mohd.; Hakim, Iqbal Ahmad (Indian Journal of Marketing, 2014)
An estimated 68.84% of the total Indian population living in villages (Census 2011) makes rural India the ’next big thing’ for businesses. The sheer size of rural India gives it a significant share in the total Indian market, which from the marketer’s perspective, translates into a huge consumer base. However, just like everything else in India, rural India too is changing. Education, access to technologies, and a progressively increasing purchasing power is the new face of rural India. While such changes uncover new opportunities for marketers, these also lead to new challenges, which so often accompany change. Based on secondary data, this paper draws conclusions with the aim to understand the changing rural consumers and markets. It also aims to identify new opportunities and challenges faced by marketers precipitated by such change. This would allow businesses to formulate an appropriate strategy focusing on customization, relationship management, distribution and promotion, which prepares the marketers to tackle and benefit from such change.